Evaluation of First-Trimester Low Percentile Nuchal Translucency Association with Adverse Perinatal Outcomes and Fetal Congenital Anomalies - Eraslan Sahin, Mefkure; Sahin, Erdem; Kirlangic, Mehmet M.; Daglituncezdi Cam, Seyma; Kutuk, Serhan; Can Ozdemir, Havva; Genc, Emre (American Journal of Perinatology, 2025)
This study aimed to evaluate the association of first-trimester low percentile nuchal translucency (NT) thickness values with adverse perinatal outcomes and fetal congenital anomalies.In this retrospective study, 2,150 pregnant women who screened first trimester NT and delivered at Kayseri City Hospital were divided into three groups based on their fetal NT thickness percentiles as follows: third percentile NT group (n: 101), 3rd to 10th percentile NT group (n: 242), and 10th to 90th percentile NT group (n: 1,807).First-trimester NT thickness was analyzed in 5 mm intervals according to gestational age, and the mean NT value was 0.76 mm in the third percentile, 0.95 mm in the 3rd to 10th percentile, 1.51 mm in the 50th percentile, and 2.36 mm in the 90th percentile. Fetal birth weight was significantly decreased in the third percentile NT group and 3rd to 10th percentile NT group compared with the 10 to 90th percentile NT group. Small for gestational age, intrauterine growth restriction with abnormal Doppler value and second-trimester spontaneous abortion rates were significantly increased in the third percentile NT group and the 3rd to 10th percentile NT group compared with the 10th to 90th percentile NT group. The study did not find an increased risk for fetal congenital anomalies in the third percentile group or the 3rd to 10th percentile group.The results indicated that first-trimester NT thickness values below the 10th percentile were associated with low fetal birth weight and adverse perinatal outcomes. Additionally, low percentile first-trimester NT thickness was not a risk factor for fetal congenital abnormalities.
Keywords: adverse perinatal outcomes; fetal birth weight; fetal congenital abnormality; low percentile first-trimester NT